A Schanuel condition for Weierstrass equations - Kirby, J (2005)
I prove a version of Schanuel's conjecture for Weierstrass equations in differential fields, answering a question of Zilber, and show that the linear independence condition in the statement cannot be relaxed. © 2005. Association for Symbolic Logic.